Impact of Inflation, Interest Rates and Return Exchange Rates on Pharmaceutical Companies on the IDX: Dampak Inflasi, Tingkat Suku Bunga dan Nilai Tukar Return Saham pada Perusahan Farmasi di BEI - Mayroza Wiska; Fenisi Resty (International Journal of Management and Business (IJMB), 2020)
Abstract In this study, researchers have conducted research at PT. Indonesia stock exchange. The purpose of this study was to determine the effect of inflation, exchange rates and interest rates on stock returns in pharmaceutical companies listed on the Indonesia Stock Exchange. By taking secondary data in the 2010-2014 period. Data analysis in this study used the classical assumption test, t-test analysis and f-test, while the overall data analysis used a computer with SPSS version 21 software.The results of this study concluded that: (1) the inflation rate partially has a positive and significant effect on stock returns in pharmaceutical companies listed on the Indonesia Stock Exchange, (2) the exchange rate partially does not have a significant effect on stock returns in listed pharmaceutical companies. in the Indonesia Stock Exchange, (3) the interest rate partially does not have a significant effect on stock returns in pharmaceutical companies listed on the Indonesia Stock Exchange, (4) the inflation rate, the exchange rate, the interest rate simultaneously influence stock returns. in pharmaceutical companies listed on the Indonesia Stock Exchange.Suggestions for companies should pay more attention to financial performance factors, both as measured by profitability and the market in determining share prices. This study can further use other methods that may be better than the variable analysis used in this study, for example logistic analysis.